2021
DOI: 10.1038/s41467-020-20337-3
|View full text |Cite
|
Sign up to set email alerts
|

The patterns of deleterious mutations during the domestication of soybean

Abstract: Globally, soybean is a major protein and oil crop. Enhancing our understanding of the soybean domestication and improvement process helps boost genomics-assisted breeding efforts. Here we present a genome-wide variation map of 10.6 million single-nucleotide polymorphisms and 1.4 million indels for 781 soybean individuals which includes 418 domesticated (Glycine max), 345 wild (Glycine soja), and 18 natural hybrid (G. max/G. soja) accessions. We describe the enhanced detection of 183 domestication-selective swe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 107 publications
2
77
0
Order By: Relevance
“…Direct comparison between corresponding chromosome sequences of the Hwangkeum and Williams 82 assemblies identified 1,788,320 SNPs and 517,907 indels (< 50 bp) (Table S6 and File S2). Interestingly, the number of SNPs is similar to the combined number (1,678,164) of heterozygous (4,919), missing (713,953), and homozygous non-reference (959,292) SNPs for Hwangkeum in the 30,753,511 SNP set without the minor allele frequency filter detected in the 781 soybean haplotype map set (Kim et al 2021). The number of indels is also similar to the combined number (470,389) of heterozygous (28,639), missing (303,784), and homozygous non-reference (137,966) indels for Hwangkeum in the 5,717,052 indel set without the minor allele frequency filtration detected from the same set.…”
Section: Genome Structure Comparison With Other Publicly Available Soybean Genomesmentioning
confidence: 69%
See 1 more Smart Citation
“…Direct comparison between corresponding chromosome sequences of the Hwangkeum and Williams 82 assemblies identified 1,788,320 SNPs and 517,907 indels (< 50 bp) (Table S6 and File S2). Interestingly, the number of SNPs is similar to the combined number (1,678,164) of heterozygous (4,919), missing (713,953), and homozygous non-reference (959,292) SNPs for Hwangkeum in the 30,753,511 SNP set without the minor allele frequency filter detected in the 781 soybean haplotype map set (Kim et al 2021). The number of indels is also similar to the combined number (470,389) of heterozygous (28,639), missing (303,784), and homozygous non-reference (137,966) indels for Hwangkeum in the 5,717,052 indel set without the minor allele frequency filtration detected from the same set.…”
Section: Genome Structure Comparison With Other Publicly Available Soybean Genomesmentioning
confidence: 69%
“…After three weeks' growth, a bulk of young trifoliolate leaf tissues was collected for genomic DNA extraction. Note that the seeds of Hwangkeum used in this study came from the line of Hwangkeum that had been subject to single plant selection at least twice during our recent 180K SoyaSNP array and genome resequencing studies (Lee et al 2015;Kim et al 2021). Genomic DNAs for the generation of Illumina short-read (Illumina, San Diego, CA, USA) and PacBio SMRT long-read sequences (Pacific Biosciences, Menlo Park, CA, USA) were extracted using the CTAB method, as described by Saghai-Maroof et al (1984).…”
Section: Plant Materials and Sequencingmentioning
confidence: 99%
“…Our estimate of nucleotide diversity loss was higher than previous estimates for domesticated sorghum based on nuclear microsatellite markers (e.g., 14%, Casa et al, 2005 ), but lower than the loss recorded in other main crops with selfing or mixed mating systems. For instance, it was estimated a 62% nucleotide diversity reduction in rice (Caicedo et al, 2007 ), 72% in common beans (Bitocchi et al, 2013 ) and 50% in soybean (Kim et al, 2021 ). Domesticated sorghum also showed lower expression variation than the wild accessions, a finding common to other crops such as maize (Lemmon et al, 2014 ) and common bean (Bellucci et al, 2014 ) but also animal domesticates (Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maldonado et al 23 sequenced 28 soybean cultivars of Brazilian, analyzed in detail the possible effects of SNPs and InDels with non-synonymous mutations on the function of the corresponding genes, and suggested that once the effect of these mutations on gene function were con rmed, then the adaptation mechanism of soybean to tropical conditions in Brazil could be explained. Kim et al 24 carried out high-depth (> 13x) whole-genome (WGS) analysis of 418 domesticated soybean cultivars, 345 wild soybean materials and 18 natural hybrid varieties. The whole genome variation map of soybean was obtained, and 10.6 million SNPs and 1.4 million InDels were identi ed.…”
Section: Introductionmentioning
confidence: 99%